Analisis Pembelajaran Daring pada saat Pandemik Covid-19 di Pendidikan Kepariwisataan - Fitriyani, Endah; Suwandi, Andreas; Gumelar, Abih (Journal of Tourism and Creativity, 2022)
The online learning process is considered a new challenge in the era of the industrial revolution 4.0, especially in the midst of a pandemic like today. This is related to the current condition of Indonesia in the midst of the Covid-19 virus outbreak where students are required to study at home. Digital-based learning models have been massively maximized in almost all of Indonesia during the pandemic. The purpose of this research is to analyze the digital-based learning model due to the COVID-19 pandemic in the online class of the Tourism Vocational School in Bandung Raya. The research method used is quantitative with descriptive study analysis of data in the form of a questionnaire. The results of the study are expected to be able to answer the problems of this research which includes the implementation of online learning during the Covid-19 virus pandemic.